PESTICIDE CONTAMINATION OF THE DRIDJI COTTON PLANTATION AREA IN THE REPUBLIC OF BÉNIN - YEHOUENOU AZEHOUN PAZOU, ELISABETH (My University, 2014)
Pesticides used for cotton production and pest control in the growing of food crops such as beans, maize and vegetables eventually may not only end up on the crops, but also in soil and surface water. As a consequence, aquatic organisms and humans consuming crops may experience pesticide exposure. This also is the case in developing countries in Africa, where pesticide use sometimes is less controlled and includes the use of older organochlorinated products. This study assessed the public health risk due to pesticide exposure along the Kiti River in the Dridji cotton-growing area in the Republic of Bénin. Aquatic organisms from the Kiti River and vegetable plants commonly consumed by the local people were analyzed for residues of organochlorinated pesticides. Kiti River sediment contained metabolites of DDT with levels up to 5.14 μg/kg dry weight. In fish, crabs and amphibians collected from the Kiti River DDT-like compounds and α-endosulfan reached levels up to 403 ng/g lipid. Leaves from beans grown in the river floodplain and consumed by the local population were contaminated with 10 pesticides including DDT-like compounds, α- endosulfan, dieldrin, lindane, hexachlorobenzene and heptachlor. Sum DDT concentrations in the bean leaves ranged between 274 and 1351 μg/kg dry weight, while these vegetables also contained endosulfan (23-210 μg/kg dry weight), dieldrin (<9-32 μg/kg dry weight) and lindane (<6 – 90 μg/kg dry weight) in high concentrations. To assess the risk to public health, pesticide intake by fish and vegetable consumption was estimated and compared with Tolerable Daily Intake (TDI) values reported by the World Health Organization. This comparison showed that fish consumption does not pose a risk for public health, but that consuming bean leaves as vegetables may lead to exceeding of TDI values. It is concluded that pesticide contamination in the Dridji cotton production area poses a risk to public health.
Keywords: Pesticides; agriculture; humans; risk; food